Successful Model of Implementing Risk Management in Supply Chain distribution Channels - Situmeang, Chandra; Nasution, Abdillah Arif; Erlina, Erlina; Rujiman, Rujiman (ExcelingTech, 2020)
The agricultural sector, especially in the highland vegetables, is considered to have potential and prospects in supporting food diversification so it must have a comparative advantage. Comparative advantage is obtained with supply chain management and risk management, therefore an optimization model is needed. However, often in agricultural activities risks are often encountered, especially in supply chain distribution channels. Risk management is very important to minimize risks that are part of supply chain management. The objectives of this study are (1) to analyze supply chain flow in the highland vegetables of Karo districtand Dairi district, North Sumatra, (2) to know the optimization and risk management model of the vegetable supply chain distribution channel in Karo District, North Sumatra, and (3) analyzing the minimalism of microcos in vegetable distribution channel of the Karo Regencyand Dairi regency, North Sumatra. The results of this study will provide an optimization model and risk management in the highland supply chain distribution channel channel to have comparative value.